Sovereign wealth funds, catalyzers for global financial markets - Vasile DEDU; Dan Costin NIȚESCU (Theoretical and Applied Economics, 2014)

(untitled)
In this paper we briefly present the impact of sovereign wealth funds on the global financial markets, the advantages they offer and the concerns they have generated lately. Sovereign wealth funds have emerged as important players in global financial markets and their stability. Although they are controlled by state, they seek to activate in the markets in the same as private investors, showing significant impact on listed companies they invest. Despite of their important presence in global financial markets, little is known about their asset allocation. Significant concerns have been expressed about SWFs limited transparency being suspected to follow other factors besides risk adjusted returns. We believe that SWFs should present clearer governance standards and more transparency in order to ensure a catalyst role for the global financial imbalances. The essential role of authorities relies on implementing an agreement on a set of regulations, standards and best practices for the sovereign wealth funds.